Estrutura de governança e agricultura familiar na cafeicultura do cerrado mineiro - Melo, Sílvio Alberto Ribeiro (2017)
In the last four decades, agricultural production in Triângulo Mineiro e Alto Paranaíba region has undergone great changes, gaining National prominence as a producer of soybeans, corn, sugar cane and coffee. The latter has been particularly important in the regional and State Economy, because its productivity is higher than the state and national average, and has significant participation in Brazilian foreign trade for this country is the largest grain producer in the world. Even with great importance in the national scenario, coffee cultivation went through several moments of prosperity and crisis over time, as in the early 1990s, with the deregulation promoted by the federal government in the sector, leading several coffee growers to seek quality improvement to the grain, as an alternative to the situation, differing from the grain commodity. There are several certifications for all types of products, and coffee is worth mentioning, since it has had a remarkable growth in these markets in the last decades, being worth highlighting the Cerrado Mineiro region, which produces high quality coffee and has, among several certifications, the Label of Origin Denomination Region of Cerrado Mineiro. For this territory to be constituted, it was necessary to create a governance structure that could guarantee producers quality control, from the planting of the grain, to the final consumer, and that this structure could be enjoyed by both medium and large producers , Such as family farmers. However, the achievement of this certification incurs high costs that end up making this process exclusive, as is the case of family farmers. So, the purpose of this assignment is to characterize the profile of the family farmers of the municipality of Patrocínio, as a reflection for the family coffee production of Cerrado Mineiro, assuming that the certification process is exclusive for the financial costs incurred in it. For this, a field survey was carried out with members of APPCER, an association of family coffee growers that has Fair Trade certification, but its members do not have the Denomination of Origin in the majority, trying to understand what difficulties they face in making sure if this is in their interest and how the governance structure in the region has an impact on their productive activity. It is concluded that, for the APPCER members, although the process is exclusive, it is not for the costs incurred in the certification, but for the lack of information about the process, however this fact can be changed within such a region as it is the Cerrado Mineiro, because it is necessary to consider how producers are inserted in the governance structure.